MAKNA PENGALAMAN BELAJAR SISWA DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Nuraini, Intan; Destrinelli; Gunawan , Indra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the meaning of students’ learning experiences in IPAS learning at the elementary school level. The research was conducted at SD Negeri 079/I Desa Teluk during the 2025/2026 academic year using a qualitative phenomenological approach. Data were collected through in-depth interviews and documentation, with the main subjects being selected sixth-grade students and supporting data obtained from the sixth-grade homeroom teacher. The results show that students’ learning experiences in IPAS learning encompass three main aspects: cognitive, affective, and psychomotor. From the cognitive aspect, students were able to understand IPAS concepts well because the learning was delivered contextually and related to everyday life. From the affective aspect, students demonstrated positive attitudes such as enthusiasm, learning interest, self-confidence, and mutual respect during the learning process. Meanwhile, from the psychomotor aspect, students were actively involved in observation, discussion, and simple practical activities that helped develop skills and strengthen their understanding of the material. These learning experiences shaped the meaning of IPAS learning as interesting, easy to understand, and beneficial for students’ lives. The meaning of students’ learning experiences in IPAS learning is influenced by internal and external factors. Internal factors include learning motivation, learning interest, and students’ learning readiness, while external factors involve the role of teachers, learning strategies, learning media, and the learning environment. Positive learning experiences have an impact on increasing students’ learning interest, active engagement, and changes in attitudes and behaviors toward greater environmental awareness. Therefore, contextually designed and student-centered IPAS learning is able to create meaningful learning experiences and improve the quality of the learning process in elementary schools.